Peer review of the pesticide risk assessment of the active substance alpha‐cypermethrin - European Food Safety Authority (EFSA); Maria Arena; Domenica Auteri; Stefania Barmaz; Alba Brancato; Daniela Brocca; Laszlo Bura; Luis Carrasco Cabrera; Arianna Chiusolo; Consuelo Civitella; Daniele Court Marques; Federica Crivellente; et al. (EFSA Journal, 2018)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Belgium and co‐rapporteur Member State Greece for the pesticide active substance alpha‐cypermethrin are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012. The conclusions were reached on the basis of the evaluation of the representative uses of alpha‐cypermethrin as an insecticide on cereals, winter oilseed rape, lettuces, leafy brassica and on cucumber and courgette in permanent glasshouses. The reliable end points, appropriate for use in regulatory risk assessment and the proposed maximum residue levels (MRLs), are presented. Missing information identified as being required by the regulatory framework is listed. Concerns are identified.